Netspeak virtual ethnography as culture in the Kaskus virtual community - Shabana, Amin (Plaridel, 2022)
Access online through this link: https://www.plarideljournal.org/article/netspeak-virtual-ethnography-as-culture-in-the-kaskus-virtual-community